Fertility in midlife women - YOLDEMİR, AHMET TEVFİK (TAYLOR & FRANCIS LTD, 2016)
Reduced maternal fertility is the consequence of depletion of follicles with maternal aging. In a 35-year-old woman, approximately 9.1% of the residual follicle pool disappears annually without entering into the growing stage, whereas, in a 45-year-old woman, this number triples. After the age of 35 years, the frequency of aneuploidies in oocytes increases sharply. Roughly 50-70% of mature oocytes from a 40-year-old woman have chromosomal abnormalities. The clinical pregnancy and implantation rates are lower in midlife women. Various controlled ovarian stimulation interventions have been suggested for the management of women in advanced age, most of whom are likely to be poor-responder patients. Currently, systematic reviews and meta-analyses suggest that there is insufficient evidence to recommend most of the treatments proposed to improve pregnancy rates in these poor responders. Minimal stimulation or natural cycle in vitro fertilization may be offered, without compromising the already existing pregnancy results.
Keywords: Fertility; midlife; advanced age; reduced fertility; AUGMENT; ovarian aging; IN-VITRO FERTILIZATION; HUMAN CHORIONIC-GONADOTROPIN; ANTI-MULLERIAN HORMONE; ADVANCED MATERNAL AGE; ASSISTED REPRODUCTIVE TECHNOLOGY; POOR-RESPONDER PATIENTS; SMALL ANTRAL FOLLICLES; OVARIAN RESPONSE; CONTROLLED-TRIAL; OOCYTE VITRIFICATION